2020
DOI: 10.1007/s00228-020-03017-5
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for treating COVID-19: a systemic review and meta-analysis of retrospective studies

Abstract: Objectives COVID-19 has become a global epidemic, and effective therapies have not been discovered up to now. We conducted this study to explore the effectiveness and safety of tocilizumab recently used for treating COVID-19. Method A comprehensive search was conducted (up to September 27, 2020), and 19 eligible records were identified according to the inclusion and exclusion criteria. The data of the studies were extracted by 2 independent reviewers and were analyzed to evaluate the safety and availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
5
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 38 publications
1
34
5
2
Order By: Relevance
“…Lan et al showed that tocilizumab could not provide additional benefits for clinical outcomes of severe COVID-19, but the mortality rate was lower than the SOC, although this was not statistically different 10 . Studies from Kaye et al, Zhao, J et al, and Zhao, M et al, reported that tocilizumab showed a statistically significant reduction in mortality and fatality than the SOC, similar to our results 9,11,13 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Lan et al showed that tocilizumab could not provide additional benefits for clinical outcomes of severe COVID-19, but the mortality rate was lower than the SOC, although this was not statistically different 10 . Studies from Kaye et al, Zhao, J et al, and Zhao, M et al, reported that tocilizumab showed a statistically significant reduction in mortality and fatality than the SOC, similar to our results 9,11,13 .…”
Section: Discussionsupporting
confidence: 92%
“…Meta-analysis on this topic has not been previously conducted; only mortality events and ICU admissions have been reported by previous studies [9][10][11]13 . In our study, we evaluate all-cause mortality events, length of stay in hospital, and days until death (time to death after first intervention) and carry out subgroup analysis of baseline criteria for administration of tocilizumab treatment.…”
Section: Strengths and Limitations Of The Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by previous meta-analysis studies on the effect of tocilizumab treatment on the mortality risk of COVID-19 patients. Khan et al [ 87 ], Rubio-Rivas et al [ 88 ], and Kotak et al [ 89 ] reported RRs [95%CIs] of 0.83 [0.72, 0.96], 0.73 [0.57, 0.93], and 0.56 [0.34, 0.92], respectively, and Zhao et al [ 90 ] and Sarfraz et al [ 91 ] reported odds ratios [95%CIs] of 0.44 [0.36, 0.55] and 0.42 [0.26, 0.69], respectively, with tocilizumab treatment compared with SOC. Despite the promising results in these meta-analysis studies, none of the four published RCTs found a significant beneficial effect on mortality rates for tocilizumab in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 , 39 , 40 An open-label study showed that tocilizumab could be safe and effective in patients in hospital with severe COVID-19, especially when applying strict selection criteria on the basis of clinical and laboratory inflammatory profiling, such as C-reactive protein, D-dimer, ferritin and lactate dehydrogenase concentrations. 40 Further data from systematic reviews and meta-analyses, including retrospective case-control studies and single-armed studies, 41 , 42 , 43 , 44 , 45 , 46 , 47 supported the addition of tocilizumab to standard of care to reduce mortality in severe COVID-19 cases.…”
Section: Antirheumatic Drugs For the Management Of Covid-19mentioning
confidence: 99%